Comparison of Volume and Distribution of Non-Agricultural Employment in the U.S.S.R., 1928-1955, with the U.S., 1870-1952 - Redding, A. David (The Review of Economics and Statistics, 1954)
A. David Redding, Comparison of Volume and Distribution of Non-Agricultural Employment in the U.S.S.R., 1928-1955, with the U.S., 1870-1952, The Review of Economics and Statistics, Vol. 36, No. 4 (Nov., 1954), pp. 444-450